Urban community garden practices as indicators of community social resilience - Harrison Taylor, Kristin (Kansas State University, 2022)
Resilience is a simple concept — bouncing back after adversity. However, defining resilience, analyzing, and understanding it is far more complex. The COVID-19 pandemic brought unexpected challenges that rippled through the food system, the social system, and the worldwide economy, exposing many vulnerabilities. It has also illuminated areas of resilience, creativity, and strength. Studies indicate that caring for urban green space (urban environmental stewardship) helps mitigate a system shock's social and ecological effects. The work done in an urban community garden is an example of urban environmental stewardship. The benefits of urban environmental stewardship and community gardens overlap as both enhance neighborhoods' social, economic, and ecological value. This mixed-methods study investigated how community gardens, as an example of urban environmental stewardship, contribute to community social resilience, particularly after a system shock. Garden leaders in the Kansas City metropolitan area participated in an online survey, online asynchronous discussion questions, and an online focus group. Discussion questions, text, and focus group transcriptions were inductively and deductively coded. Deductive coding used McMillen et al. (2016) indicators of community social resilience: place attachment, collective identity, social cohesion, social networks, and knowledge exchange and diversification. Inductive coding of the complete data set (all discussion and focus group responses) and within each question was done to look for themes across the data sets. Results show that community garden practices align well with the theoretical framework (McMillen et al., 2016) and illuminate how community gardens contribute to community social resilience. Furthermore, results highlight broader links between community gardens and human well-being.
Keywords: Community social resilience; Community gardening; System shock/crisis; Social impacts of community gardening; Human health and well-being; Urban environmental stewardship